Translation, cross-cultural adaptation, and validation of the Palliative Care Knowledge Questionnaire for PEACE (PEACE-Q) in Brazilian Portuguese - João Paulo Aureliano Silva; Aleida Nazareth Soares; Adriana Silvina Pagano; Cristiana Guimarães Paes Savoi; Alexandre Ernesto Silva; Alexandre Sampaio Moura (Einstein (São Paulo))
ABSTRACT Objective: To translate, cross-culturally adapt, and validate the Palliative Care Knowledge Questionnaire for PEACE (PEACE-Q) in Brazilian Portuguese. Methods: This study followed five steps: translation, back-translation, cultural adaptation, pre-test, and test-retest. Pre-test (n=20) and test-retest (n=63) were conducted on medical residents from Santa Casa Hospital in Belo Horizonte, Brazil. We determined the content validity index, Kuder-Richardson-20 (KR-20) value, and intraclass correlation coefficient. The performances of residents with different years of training and specialty areas were compared using the Kruskal-Wallis and Mann-Whitney tests. Results: The translated version of the instrument comprised 33 items divided into nine domains, with a content validity index of 0.95. The test-retest on medical residents showed an internal consistency (KR-20) of 0.60 (95% confidence interval (95%CI)=0.54-0.66) and intraclass correlation coefficient of 0.71 (95%CI=0.51-0.82). Medical residents of clinical specialties showed better overall scores than those of surgical or mixed specialties (median scores [IQR]: 27.0 [25.0-28.0], 26.0 [23.0-28.0], and 23.5 [21.5-25.5], respectively; [p=0.013]). Regarding year of training, medical residents on year three or beyond had higher scores in the "Opioid Side Effects" domain than those on the first 2 years [median scores (IQR): 2.0 (2.0-3.0) versus 2.0 (1.0-2.0); p=0.03]. Conclusion: The Brazilian version of the PEACE-Q demonstrated acceptable internal consistency and moderate reliability and appears appropriate for assessing the palliative care knowledge of Brazilian medical residents.